Donasi sebagai Ekspresi Afeksi: Pengalaman Psikologis Penggemar V-tuber Dewasa (Studi Kualitatif) - Nasrullah, muhammad ilyas (CERDAS AKADEMIKA NUSANTARA, 2025)
This qualitative study investigates the psychological experiences of adult V-tuber fans who donate to their virtual idols, focusing on how donation functions as an expression of affection. Employing a thematic analysis approach, data were collected via semi-structured in-depth interviews with 15 adult donors selected through purposive and snowball sampling. Interview transcripts were analyzed inductively to identify core themes regarding donation motives, affective meaning, parasocial dynamics, and the psychological and financial impacts on participants' daily lives. Findings reveal four central themes: (1) donation as an expression of emotional support and appreciation; (2) donation as a means of fandom identity construction and social recognition; (3) parasocial interaction mediated by streamer responsiveness, which amplifies donation drives through emotional rewards; and (4) tension between affective satisfaction and financial/psychological costs (e.g., regret, impulse control issues). The study highlights the complex affective motivations underpinning the digital gift economy and their implications for fan well-being and community practices. Recommendations are offered for platform designers, mental health practitioners, and media researchers: implement consumer-protection mechanisms and financial-literacy interventions, and incorporate identity-affect considerations in mental-health supports. Future research should adopt longitudinal and cross-cultural designs. Keywords: V-tuber, donation, parasocial relationship, gift economy, psychological experience, thematic analysis.